Biomass energy in developing countries problems and challenges - Goodman, Gordon T.
Shortages of woodfuels in developing countries are generated by the complex interaction of many conditioning factors-environmental, economic, demographic, sociopolitical and cultural-leading to a site-specificity that defies generalization. Solutions involve using existing wood resources as efficiently as possible in order to buy the time needed to switch over in the towns to electricity, kerosene and bottled gas and to stimulate all forms of wood-fuel generating landuse practices including agroforestry among farmers in the rural areas. Foresters have an important cooperative role to play with agriculturalists in the agroforestry solution. It would be a tragic waste of scarce resources, if in the absence of this, agriculturalists were forced to "reinvent the silvicultural wheel."